2011
DOI: 10.1177/1528083710396263
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Fabrics for Structural Composites

Abstract: This article gives an insight into the design considerations that have been considered to design a technical hybrid fabric structure for Radome application. An attempt has been made to study empirical relationship between various structural parameters that have a major influence on the final composite properties. The hybrid fabric structures woven out of E-glass (warp) and PEEK Downloaded from (weft) and E-glass (warp) and polyester (weft) have been designed based on mathematical approach and expressed in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The tightly woven fabrics are typically the choice to maintaining fibre orientation during the manufacturing process and minimizing resin void size due to the shorter impregnation distance. Therefore, the laminar and crosswise flow of resin along and between the fibres, in between the yarns and fabric layers is easier [24,25]. Moreover, basket weave has higher quantity of interlace points per unit area compared to satin.…”
Section: Composite Porositymentioning
confidence: 98%
“…The tightly woven fabrics are typically the choice to maintaining fibre orientation during the manufacturing process and minimizing resin void size due to the shorter impregnation distance. Therefore, the laminar and crosswise flow of resin along and between the fibres, in between the yarns and fabric layers is easier [24,25]. Moreover, basket weave has higher quantity of interlace points per unit area compared to satin.…”
Section: Composite Porositymentioning
confidence: 98%
“…In the past decades, the automotive industry had to deal with two major issues concerning these biobased-composites: i) the ability to process the composite parts both in one step process and reduced production time, ii) by keeping a good quality of obtained structures (resistance to mechanical loading, for example). Nowadays, only few manufacturing processes such as light resin transfer molding (light RTM) or thermalcompression are considered by this industry [9][10][11]. When using conventional heating equipment such as a hot press Picher-Martel et al [12] showed that short carbon fibre/PEEK structures were successfully obtained by thermo-compression in about 40 min at 400°C which is the melting temperature of the resin [12].…”
Section: Introductionmentioning
confidence: 99%
“…Except for direct polymer melting methods, such as pultrusion and co-extrusion [34,35], currently, there are two main technologies that can be used for continuous fiber-reinforced thermoplastic polymer matrix composite production. One of them is bringing the fiber as close as possible to the thermoplastic polymer matrix before the composite consolidation, which includes powder impregnation [36][37][38], commingled yarn fabrication [39,40], cowoven fabric producing [41,42], and film stacking method [43][44][45] technologies, to reduce void and improve the matrix distribution. The other is synthesizing the thermoplastic polymer matrix directly in the composite fabrication step, such as in situ polymerization, due to the easier process of impregnation of the fiber bundles with low viscosity polymer precursors [46][47][48].…”
Section: Introductionmentioning
confidence: 99%